1998
DOI: 10.1152/ajpregu.1998.275.4.r1152
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH regulation in neurons from chemosensitive and nonchemosensitive areas of the medulla

Abstract: brain stem; central chemoreceptor; carbon dioxide; fluorescence imaging; respiration; Na ϩ /H ϩ exchange THE LEVEL OF CO 2 /H ϩ in the blood is carefully regulated by certain neurons in several areas of the medulla oblongata. These neurons are collectively known as central chemoreceptors. The areas in which these neurons are located are known as chemosensitive areas and include the ventrolateral medulla (VLM), the nucleus of the solitary tract (NTS), and the medullary raphe (16). It is hypothesized that an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
98
2
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(114 citation statements)
references
References 29 publications
12
98
2
2
Order By: Relevance
“…1B, solid squares). These findings are consistent with Na ϩ /H ϩ (NHE) exchange playing a predominant role in pH i recovery in SC neurons from adults, as it does in SC neurons from neonates (41,42). However, we were not able to study pH i recovery more fully in adult SC neurons since the pH-transporter inhibitors amiloride and 4,4Ј-diisothiocyanatostilbene-2,2Ј-disulfonic acid (DIDS) interfered with pyranine fluorescence.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…1B, solid squares). These findings are consistent with Na ϩ /H ϩ (NHE) exchange playing a predominant role in pH i recovery in SC neurons from adults, as it does in SC neurons from neonates (41,42). However, we were not able to study pH i recovery more fully in adult SC neurons since the pH-transporter inhibitors amiloride and 4,4Ј-diisothiocyanatostilbene-2,2Ј-disulfonic acid (DIDS) interfered with pyranine fluorescence.…”
Section: Resultssupporting
confidence: 73%
“…The normal response of pH i to an NH 4 Cl prepulse is a rapid alkalinization followed by an acidification in the absence of any change in extracellular pH (2,42). We found that the response to NH 4 Cl of SC neurons from adult rats was similar to that of SC neurons from neonatal rats (41,42). Adult SC neurons exhibited a rapid pH i recovery from an NH 4 Cl prepulse induced acidification that returned toward the initial pH i (Fig.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…The effect of 60 mins perfusion with 20 mmol/L glucose/anoxia are shown in Figures 5F to 5G, which show that this condition has no significant effect on the integrity of processes assessed using the fluorescence technique. Perfusion with sodium propionate (20 mmol/L), which will evoke an intracellular acid shift similar to that produced by OGD (Ritucci et al, 1998), was also without significant effect on process fluorescence (data not shown).…”
Section: Validation Of the Use Of Green Fluorescent Protein Imaging Tmentioning
confidence: 91%